Cellular structure assisted enhanced deformation-induced martensitic transformation in laser-directed energy deposited ferrous medium-entropy alloy - Kim E.S.; Ahn S.Y.; Jeong S.G.; Go E.-H.; Bae J.W.; Hong S.-J.; Wang J.; Lee B.-J.; Karthik G.M.; Kim H.S. (My University, 2025)
The effect of cellular structure on the deformation behavior of laser-directed energy deposited Fe60(CoNi)30Cr10 medium-entropy alloys was comprehensively analyzed. High dislocation density and elemental segregation at cellular boundaries significantly promoted deformation-induced martensitic transformation and enhanced heterogeneous deformation-induced strengthening. This highlights the potential to optimize the mechanical performance of the alloy through cellular engineering. © 2024 Elsevier B.V.